The Effect of Housing Locations Towards Off-Campus Students’ Travel Behaviour - Muhammad Amir Hafiz Aziz; Nur Sabahiah Abdul Sukor (International Journal of Integrated Engineering, 2026)
University students exhibit distinctive travel characteristics. Lately, the residential trends among university students in Malaysia, particularly those who live off-campus undergone a significant transformation. This study aims to analyze the effect of student housing location on the way they navigate their daily commutes. The methodology employs statistical analyses and spatial mapping techniques. Multiple variables were explored, including sociodemographic characteristics, residential locations, transport mode preferences, commuting patterns, and attitudinal tendencies of off-campus students at the Engineering Campus, USM. Data were obtained through an online questionnaire involving 190 participants, analysed using descriptive statistics and Pearson correlation to identify potential interrelationships among the variables. Additionally, QGIS-based spatial mapping techniques were used to visualise the spatial distribution of housing locations and corresponding mobility flows. Findings suggest that proximity and accessibility of accommodation relative to the campus may play a central role in shaping students’ commuting choices. Interestingly, students residing nearer to the campus appeared more inclined towards active travel modes, such as walking and cycling, whereas those living further away displayed a stronger reliance on motorised transportation.